Answer:
[tex]\mathrm{The\:solutions\:to\:the\:system\:of\:equations\:are:}[/tex]
[tex]x=2,\:y=-1[/tex]
Step-by-step explanation:
Considering the system of the equation
[tex]\begin{bmatrix}y=-2x+3\\ 4x-3y=11\end{bmatrix}[/tex]
[tex]\mathrm{Subsititute\:}y=-2x+3[/tex]
[tex]\begin{bmatrix}4x-3\left(-2x+3\right)=11\end{bmatrix}[/tex]
[tex]\mathrm{Isolate}\:x\:\mathrm{for}\:4x-3\left(-2x+3\right)=11[/tex]
[tex]4x-3\left(-2x+3\right)=11[/tex]
[tex]4x+6x-9=11[/tex]
[tex]10x-9=11[/tex]
[tex]10x-9+9=11+9[/tex]
[tex]10x=20[/tex]
[tex]x=2[/tex]
[tex]\mathrm{For\:}y=-2x+3[/tex]
[tex]\mathrm{Subsititute\:}x=2[/tex]
[tex]y=-2\cdot \:2+3[/tex]
[tex]y=-1[/tex]
[tex]\mathrm{The\:solutions\:to\:the\:system\:of\:equations\:are:}[/tex]
[tex]x=2,\:y=-1[/tex]